(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
The article exposes the concepts of anthropocene and ecology in relation to theatrical art, to discuss possibilities that artists have to produce ideas and values in line with the ecological urgency in individual and collective relationships between human beings and nature. Through three paths, as a means of constituting scenic relationships in theatre, the author questions about human actions, their limits and scope in relation to global planetary transformations, possible to be represented and sensitized on stage, from the theme, the scenographic and spatial design to the aesthetic design.